Status Sosial Ekonomi dan Pengeluaran OOP Kesehatan Penyandang Disabilitas - Nainggolan, Maxent RG; Relaksana, Riki (Jurnal Ekonomi Kesehatan Indonesia, 2025)
In 2020, the number of persons with disabilities in Indonesia reached 22.97 million. One of the main challenges this population faces is the high burden of health expenditures, particularly those that are urgent and unpredictable. This study aims to analyze the influence of socioeconomic status on out-of-pocket (OOP) health expenditures among households with persons with disabilities in Indonesia. A quantitative approach was employed using secondary data from the 2022 National Socioeconomic Survey (Susenas), utilizing the core module (KOR) and the household expenditure module (KP). Data were analyzed using the two-part regression model to identify the determinants of OOP health spending. The results indicate that total household expenditure, educational attainment, and age of persons with disabilities are positively and significantly associated with higher OOP health expenditures. Conversely, health insurance ownership negatively and significantly affects OOP spending. These findings highlight the importance of social protection policies and expanded access to health insurance in reducing the economic burden on households with disabled members.